Remuneration policy for lower-rank professional civil servant : a case study of Southern Thailand - Sadama, Azeezah
This research sought to identify the effectiveness of Thailand's 2015 remuneration policy implemented by the government of Prayut Chan-o-cha in motivating civil servants towards better job performance. Guided by expectancy theory, a questionnaire is designed to measure perception on the 2015 remuneration policy as well as civil servants' perceived performance after the implementation of this policy. 250 copies of the questionnaire were collected from the lower-rank civil servants from 5 different provinces within Southern Thailand. The analysis shows that vast majority of civil servants agree with the policy and there is a significant improvement in their work performance due to the policy. In addition, through the use of Pearson's coefficient correlation, the analysis signifies a strong positive relationship between perceived incentive and perceived performance of civil servants. This implies that the performance of Thailand's civil servants can be improved further if the right incentive was to be given.